T22. Intra-operative motor mapping using subdural grid electrodes in children undergoing invasive EEG monitoring. (May 2018) - Jain, Puneet; Whitney, Robyn; McCoy, Blathnaid; Ochi, Ayako; Otsubo, Hiroshi; Snead, Carter; Weiss, Shelly; Donner, Elizabeth; Strantzas, Samuel; Pang, Elizabeth; Sharma, Rohit; Viljoen, Amrita; et al.
Abstract : Introduction: Extra-operative motor mapping (EOMM) in the pediatric population can be challenging, especially in young and/or developmentally delayed children, due to lack of cooperation, and higher motor stimulation thresholds. This study examined the feasibility and safety of intra-operative motor mapping (IOMM) using subdural grid electrodes in children undergoing epilepsy surgery evaluation. Methods: Twenty consecutive children under18 years of age with drug refractory epilepsy who underwent invasive EEG monitoring using subdural grid placement and intra-operative motor mapping at our institution between December 2015 and June 2017 were enrolled. Stimulation was delivered to the subdural grid electrode using a train of five pulses, with an interstimulus interval of 1.1 ms and a pulse duration of 50 microseconds. Stimulation intensity was commenced at 25 Volts (V) and increased gradually until acceptable motor evoked potential (MEP) waveforms were generated. MEPs were recorded from the contralateral six muscle groups (orbicularis oris, deltoid, extensor digitorum communis, first dorsal interossei, tibialis anterior and abductor halluces). Extra-operative motor mapping (previously published procedure) was also done 3 days after the subdural grid placement. Results: IOMM using sub-dural grid electrodes was completed in 20 patients, and simultaneous EOMM was done in 17 patients. The mean age at the time of mapping was 11.7 years (SD 4.2). 13/20 patients had malformations of cortical development. MEP responses were more commonly obtained in the deltoid (19/20), extensor digitorum communis (20/20) and first dorsal inerossei (19/20). The mean threshold varied from 44.5 V to 55.8 V for the six muscle groups. With increasing age, there was a decline in the motor thresholds with a possible exponential relationship. No seizures or anaesthesia related complications were noted. EOMM could not be completed in 4/17 children (3-clinical seizures, 1-limited patient cooperation). The mapping was incomplete in the majority of cases with 1 being the median number of areas mapped (IQR, 1–2). Seizures were seen in 6/17 (35.3%) and after-discharges in 7/17 (41.2%) children. Nine patients demonstrated 100% concordance between the common mapped areas, 4 patients showed 50% concordance and 3 patients showed no concordance between IOMM and EOMM. The median duration of follow up was 10.2 months (IQR, 3.6 to 14.4 months). ILAE seizure outcome 1 was seen in 15 patients (75%) at the last follow up. Post-operative neurological deficits were seen in 11 patients: contralateral motor deficits (6; 2 were transient), contralateral sensory deficits (2), homonymous hemianopia (1) and seizures (3). Conclusion: IOMM was found to be feasible and safe procedure in children with drug refractory epilepsy undergoing invasive EEG monitoring using the subdural grid.